Front-end electronics for the GAPS tracker - Manghisoni, Massimo; Re, Valerio; Riceputi, Elisa (Sissa Medialab Srl, 2019)
The General Antiparticle Spectrometer (GAPS) is an Antarctic balloon-borne mission to indirectly search for dark matter through sensitive observation of cosmic antiparticles. The first flight is planned for late 2021. GAPS is the first experiment optimized specifically for detection of low-energy (< 0.25 GeV/n) antideuterons, which are recognized as distinctive signals from dark matter annihilation or decay in the Galactic halo. To achieve high sensitivity to cosmic antinuclei in this low-energy range, GAPS uses a novel particle identification method based on exotic atom capture and decay. The GAPS instrument consists of ten planes of 1440 10 cm-diameter, 2.5 mm-thick, 8-strip lithium drifted silicon (Si(Li)) detectors, which constitutes the tracker, surrounded by a plastic scintillator time-of-flight system. A new fabrication technique has been developed to satisfy the stringent requirements of the mission. In this contribution, we describe the front-end electronics of the tracker of GAPS. The system is composed of front-end ASICs and power supplies. The ASICs provide readout and digitization of the signal (with an 11-bit ADC) in a wide dynamic range (10 keV - 100 MeV). Every ASIC has 32 channels and performs the readout for 4 detectors, for a total amount of 11520 channels. The ASIC analog front-end is based on a dynamic compression technique to handle a large range of signal amplitudes and features a low noise performance, achieving the required 4 keV resolution at low energies. The power system supplies both bias voltages for the Si(Li) detectors and low voltages for the electronics.